2004
DOI: 10.1111/j.0036-9292.2004.05101005.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Computer Use On Earnings in the UK

Abstract: The effect of new technology on relative demands for workers has been the subject of much research in economics. Krueger (1993) and others have studied the impact of computers on earnings in the US and elsewhere. Such studies have been criticised for ignoring the possibility of bias due to unobserved heterogeneity between computer users and non-users, resulting in computer users not being a random subsample of all workers. As well as looking at the effects of computers on earnings in the UK, this paper extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The data served the expansion of the view that IT related trainings can be viewed as an important element in impacting IT investments as discussed by several prior studies which indicate that IT investments are often associated with increased in training effort (Bartel et al, 1987;Laudon & Laudon, 1998;Brynjolfosson & Hitt, 1998;Bartel & Sicherman, 1998;Arabsheibani et al, 2004;Loo et al, 2005;Moriones & Lopez, 2007). Through effective IT related trainings applied to all employees, it appears to predict IT investments.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The data served the expansion of the view that IT related trainings can be viewed as an important element in impacting IT investments as discussed by several prior studies which indicate that IT investments are often associated with increased in training effort (Bartel et al, 1987;Laudon & Laudon, 1998;Brynjolfosson & Hitt, 1998;Bartel & Sicherman, 1998;Arabsheibani et al, 2004;Loo et al, 2005;Moriones & Lopez, 2007). Through effective IT related trainings applied to all employees, it appears to predict IT investments.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…Since IT investments involve the high provision (Khor, 1999), employees must have sufficient IT skills (Brynjolfsson and Hitt, 1998;Arabsheibani et al, 2004;Moriones & Lopez, 2007) so that it will increase productivity as well as provide good returns to the organizations (Bates, Holton & Seyler, 1996). Therefore, the management of organization plays an important role in providing more IT trainings to enhance the IT skills of the employees (Baldwin et al, 2004).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabsheibani et al (2004) using 1980s data from the British Social Attitudes Survey, found large returns (22% to 26%), rising to a surprising 37% when seemingly taking account of selection. Arabsheibani and Marin (2006), however, using the 5 th sweep of the National Child Development Study (NCDS) in 1991, report lower estimates ranging from 7 to 17%.…”
Section: Introductionmentioning
confidence: 99%
“…Using the National Longitudinal Survey of Youth for the years 2000, and 2006, Danyal et al (2011 implement a fixed-effects model and find that individuals possessing computer skills (defined as having a personal computer at home) earn a 4.8% wage premium. Arabsheibani et al (2004) use data from the British Social Attitudes Survey for 1985 and 1990 and implement the Heckit technique to correct for selectivity bias. Their results show that two-thirds of the wage differential between computer users and non-users is explained by computer use.…”
Section: Introductionmentioning
confidence: 99%